In vitro studies evaluating the efficacy of mouth rinses on Sars-Cov-2: A systematic review - Jyothi Tadakamadla; Elisa Boccalari; Vatsna Rathore; Carolina Dolci; Gianluca M. Tartaglia; Santosh Kumar Tadakamadla (Elsevier, 2021)
This systematic review aims to evaluate the evidence on the efficacy of mouth rinses on SARS-CoV-2 from in vitro studies. Five electronic databases were searched up to February 2021; no language or time restrictions were used. Two independent reviewers conducted both selection and data extraction processes. The toxicological data reliability assessment tool was used to evaluate the risk of bias. Starting from 239 articles, retrieved by the electronic search, only eight studies were included in our systematic review. Povidone Iodine (PVP-I) was effective in killing SARS-CoV-2, demonstrated higher virucidal activity than other commonly used active ingredients. Conflicting results were found about the effectiveness of Chlorhexidine (CHX) while hydrogen peroxide (H2O2) proved less effective than PVP-I. Other active ingredients, such as quaternary ammonium compounds and Ethanol (particularly when combined with essential oils), have also shown promising results in reducing viral load, with results comparable to PVP-I.